EVALUATION OF DEFOLIANTS TO FACILITATE MECHANICAL PICKING IN RAINFED COTTON - K , ASHOK KUMAR (The Journal of Research ANGRAU, 2026)
A field experiment was conducted during the kharif season of 2024 at Regional Agricultural Research Station, Nandyal to evaluate the effect of defoliants on facilitating mechanical picking in cotton.The treatments consisted of T1 :Control, T2 :Ethrel@3000ppm,T3 :Thidiazuron@500ppm, T4 :Sodiumchlorate@0.9%, T5 :CICRDefoliant, T6 :Hydrogencyanamide @5000ppm, T7 :T2 +5%ofurea, T8 :T2 +Diuron@400 ppm, T9 :T2 +Sodiumchlorate @0.9% and T10 :T3 +Diuron@400ppm. Higher percent defoliation (95.5) at 10 days after spraying was recorded with T3 (Thidiazuron @500 ppm) and was on par withT10 (93.1) followed byT9 (89.5), T5 (86.2) and lower percent defoliation (5.3) was recorded with T1 (Control). Further, higher earliness index (75%) was recorded with T10 (Thidiazuron@500ppm+Diuron @ 400ppm) and was on par T3 (72%) followed by T4 (65%);and lower earliness index(38)was recorded with T1 (Control). It can be concluded that higher defoliation was attained with application of Thidiazuron @500 ppm+ Diuron @400ppm and also higher cotton seed yield. There was considerable correlation between defoliation at 5 DAS and 10 DAS. Further, the quality parameters were not significantly effected due to defoliants application.